Bunching of residential building energy performance certificates at threshold values. (1st February 2018) - Collins, Matthew; Curtis, John
Highlights: Examines energy performance certificate (EPC) pre and post energy efficiency retrofit. Bunching in distribution of post-works EPCs but not in the equivalent pre-works EPCs. Use a regression discontinuity design and estimate counter-factual distribution of EPCs. Find no evidence of illicit behaviour by EPC assessors. High rates of low energy lights prevalent among EPC in bunching areas of distribution. Abstract: Energy performance certificates (EPC) provide a measure of and raise awareness of the energy efficiency of homes. The Irish system of energy performance certificates comprises fifteen alpha-numeric grades, which imposes fourteen discrete notches in an otherwise continuous scale. Visual evidence of bunching occurs in the distribution of EPC certificates on the favourable side of EPC grades among homes that have completed energy efficiency retrofits but not in the equivalent distribution of EPC certificates prior to completion of retrofits. Using a regression discontinuity design and estimation of a counter-factual distribution, evidence is found of bunching in the post-works distribution but not the pre-works distribution. We analyse whether statistical evidence exists of drivers of this bunching and whether sources of bunching can be identified. We find that bunching is widespread but not systemic and find discontinuities in the distribution of certain parameters of assessment (i.e. low energy lighting) which suggests their contribution toward bunching. With comparable EPC schemes across Europe the results have policy implications for other countries. Where continuous EPC scales are used, additional energy efficiency improvements may be achieved if a multi-point scale is considered. In countries where multi-point EPC scales are used, bunching of assessments is also likely to occur and quality control measures may be necessary to ensure that the bunching is due to genuine energy efficiency improvements and not a reflection of illicit activity.